Discriminant value of automated leucocyte VCS parameters in the detection of tropical infections. Issue 4 (4th February 2021) - Muthunatarajan, Shruthi; Basavaiah, Sridevi Hanaganahalli; Shenoy, Suchitra M.; Natarajan, Arvind; Mithra, Prasanna; Suresh, Pooja Kundapur; Sreeram, Saraswathy
Abstract : Introduction: In India, infectious diseases are a leading treatable cause of morbidity and mortality. Mangalore being endemic to many vector‐borne diseases, their incidence is known to show seasonal variations with sharp increase during monsoon. Leucocytes have substantial role in the immunological pathogenesis of infections. Methods: The present series was a hospital‐based cross‐sectional study performed in a tertiary care hospital for a period of three months from June‐August wherein the cell population data of cases of malaria, dengue, leptospirosis, typhoid and rickettsial infections along with equal number of healthy controls were collected and analysed. Effectiveness of leucocyte‐related volume (V), conductivity (C) and scatter (S) parameters by Coulter®DXH800 haematology analyser in predicting these infections was appraised. Results: A total of 324 cases comprising of malaria (50%), dengue (30.9%), leptospirosis (13.9%), typhoid (4.0%) and rickettsial infections (1.2%) were included. There was statistically significant differences ( P  < 0.05) in the mean values of complete blood count parameters—haemoglobin, total leucocyte count, red blood cell count, haematocrit, red cell distribution width, differential leucocyte count, platelet count and plateletcrit between cases and controls and also between specific infections. The mean volumes of neutrophil, monocyte and lymphocyte were considerably increased in malaria and dengue fever compared to leptospirosis, typhoid and rickettsial infections. VCS parameters were the least altered in typhoid fever, except for a strikingly high conductivity and scatter of eosinophils. Conclusions: Haematological analysis is a part of routine evaluation of any case of febrile illness. This study showed that there are specific alterations in VCS parameters in different types of infections such as malaria, dengue, leptospira, typhoid and rickettsia, the information and analysis of which comes without any additional cost. Abstract : It is a hospital‐based cross‐sectional study. Single largest study from Indian subcontinent. VCS data of cases of malaria, dengue, leptospirosis, typhoid and rickettsial infections were analysed. Equal number of healthy controls were collected and analysed. Utility of leucocyte related volume (V), conductivity (C) and scatter (S) parameters by Coulter®DXH800 haematology analyser in predicting these infections was evaluated. Total number of subjects on which VCS data were analysed was 648. Statistically significant differences ( P  < 0.05) in the mean values of complete blood count parameters were obtained. The parameters were Hb, WBC count, RBC count, HCT, RDW, PC, DLC and PCT. The values were significant between controls and cases and also between specific infections. The mean volumes of neutrophil, monocyte and lymphocyte were increased significantly in malaria and dengue fever. Dengue cases showed significantly higher values in most of the leucocyte light scatter data. Typhoid fever showed strikingly high conductivity and scatter of eosinophils. Typhoid fever showed near normal values in rest of the VCS parameters. There are specific changes in VCS parameters in different types of infections. The information and analysis of VCS data comes without any additional cost.